Thiamine improves in vitro propagation of sweetpotato [Ipomoea batatas (L.) Lam.] – confirmed with a wide range of genotypes - Vollmer, R.; Espirilla, J.; Sánchez, J.C.; Arroyo, L.; Acosta, M.; Flores, G.; Rojas, A.; Ellis, David; Azevedo, V.C.R. (Springer, 2023)
In vitro propagation of Plant Genetic Resources is a basic step for routine genebank and biotechnology research activities. Accelerating growth and rooting of in vitro plants contributes to an improvement in process efciency and plant quality. In the present study the efect of supplemental thiamine and explant size on biometric variables, ion content in plant sap, chlorophyll content in leaves and moisture content in plants were assessed in a replicated trial on a group of seven in vitro sweetpotato accessions and validated in a set of other 45 accessions. It was shown that adding 0.1 mg L −1 of thiamine to modifed Murashige and Skoog culture medium signifcantly increased plant height, root length, and number of nodes of in vitro sweetpotato shoot culture plants. No signifcant diferences were observed for N03 −, K+, Na+ and Ca++—ion content in plant sap, nor in leaf area, chlorophyll, or moisture content between plants grown with or without thiamine. Uninodal stem segments showed on thiamine-free medium a signifcantly lower root and plant growth, and reduced number of nodes, than plants grown from uni- and binodal segments on thiamine-supplemented medium. A subsequent experiment tested all the parameters above in a non-replicated screen with a set of 45 diverse sweetpotato accessions. With this diverse set of germplasm, the average plant and root length increased by 41 and 51%, respectively on thiamine-supplemented culture medium compared to the control treatment, confrming that supplemental thiamine is generally benefcial to sweetpotato in vitro shoot culture.